2005
DOI: 10.5713/ajas.2006.252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic or Inorganic Acid Supplementation on Growth Performance, Nutrient Digestibility and White Blood Cell Counts in Weanling Pigs

Abstract: Four experiments were conducted to investigate the effect of organic or inorganic acid supplementation on the growth performance, nutrient digestibility, intestinal measurements and white blood cell counts of weanling pigs. In growth trial (Exp I), a total of 100 crossbred pigs ({Landrace×Yorkshire}×Duroc), weaned at 23±2 days of age and 7.25±0.10 kg average initial body weight (BW), were allotted to 5 treatments by body weight and sex in a randomized complete block (RCB) design. Three different organic acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 42 publications
3
18
0
1
Order By: Relevance
“…In the present study DM, nitrogen and energy digestibility were not affected with organic acid supplements which are consistent with the findings of Kil et al (2006) and Radecki et al (1988) who indicated that DM and CP were not improved by organic acid such as formic, fumaric or lactic acid. In contrast, other researcher observed favourable effect on nutrient digestibility with organic acid supplementation such as 2% benzoic acid in the diet of lactating sows (Kluge et al 2010).…”
Section: Resultssupporting
confidence: 95%
“…In the present study DM, nitrogen and energy digestibility were not affected with organic acid supplements which are consistent with the findings of Kil et al (2006) and Radecki et al (1988) who indicated that DM and CP were not improved by organic acid such as formic, fumaric or lactic acid. In contrast, other researcher observed favourable effect on nutrient digestibility with organic acid supplementation such as 2% benzoic acid in the diet of lactating sows (Kluge et al 2010).…”
Section: Resultssupporting
confidence: 95%
“…This may reduce the total quantity of faecal protein and hence increase the digestibility of nitrogen and also of DM and E, as an indirect consequence. However, in the present study, nitrogen and energy digestibility were apparently not improved by organic acid supplementation, consistent with the findings of Kil et al (2006) and Radecki et al (1988), who reported that DM and CP were not improved by the addition of organic acids such as formic, fumaric, or lactic acid. In contrast, other researchers have observed favourable effects on nutrient digestibility with organic acid supplementation (Franco et al 2005).…”
Section: Effects Of Protected Organic Acidssupporting
confidence: 82%
“…However, the N and energy digestibility in this study were not improved by the blend of OA and MCFA supplementation. In contrast, other studies reported that the DM digestibility was not affected with dietary supplementation of the same product in laying hens [20], organic acids such as formic, fumaric, or lactic acid in pigs [42,43]. Moreover, it was found that the metabolizable coefficients of gross energy and N had increased in broilers fed OAs [40,44] compared to those fed diets without OAs.…”
Section: Nutrient Digestibilitymentioning
confidence: 81%